2015
DOI: 10.5296/jei.v1i1.7703
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Students’ Perceived Barriers that Slow the Progress toward Completing a Doctoral Dissertation: A Mixed Analysis

Abstract: <p>The non-completion of doctoral degrees has been a concern due to its economic, social, and personal consequences. In the current study, the researchers investigated perceived barriers of select doctoral students in completing their doctoral degrees by utilizing a fully mixed sequential mixed research design. The quantitative and qualitative data were concurrently collected using identical samples (<em>n </em>= 205) via a Reading Interest Survey questionnaire. A sequential mixed analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…The results show that the participants face some personal challenges, such as anxiety, stress, lack of motivation, and time management problems. These findings are similar to the ones in the recent literature (Bireda, 2015;Hwang et al, 2015;Kakupa, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results show that the participants face some personal challenges, such as anxiety, stress, lack of motivation, and time management problems. These findings are similar to the ones in the recent literature (Bireda, 2015;Hwang et al, 2015;Kakupa, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…As a result, the low level of proficiency prevents them from making a sufficient discussion in the target language (Al Fadda, 2012). Consequently, PhD candidates may encounter negative feelings such as stress (Al Fadda, 2012;Moate et al, 2019) and lack of motivation (Hwang et al, 2015). These negative emotions might force some of them to leave the doctoral program (Hunter & Devine, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, this suggests that the problem is worsening and has not yet received the attention it deserves. This is in concert with findings in other contexts where study delays are shown to be the most common manifestations of doctoral programs (Akparep et al, 2017;El-Ghoroury et al, 2012;Hwang et al, 2015;Lindsay, 2015;Pyhältö et al, 2012;van de Schoot et al, 2013). Reviewing the situation in various doctoral programs in the US, Hwang et al (2015), for example, note that PhD students complete their studies within seven to 10 years.…”
Section: Discussionsupporting
confidence: 73%
“…Several challenges were reported in the literature that contributed to the difficulty of doctoral journey. For example, although the doctoral students' abilities to have a school-life balance is an important indicator for degree completion, doctoral students are more likely to experience a lack of school-life balance due to several reasons that include doctoral program requirements and family obligations (Alkathiri & Olson, 2019;Hwang et al, 2015;Martinez, Ordu, Della Sala, & McFarlane, 2013;Stimpson & Filer, 2011;Sverdlik, Hall, McAlpine, & Hubbard, 2018).…”
Section: Challenging Journey For Doctoral Studentsmentioning
confidence: 99%